Input–Output Analysis: Measuring the Multiplier Effect of The Mining Sector on The Economy of East Kalimantan - Diana Lestari; Ayat Nur Hidayat; Rangga Aji Wijaksono (Lafadz Jaya Publisher, 2026)
The economy of East Kalimantan remains highly dependent on the Mining and Quarrying sector; however, in recent periods, the role of other sectors, such as the Manufacturing sector, has begun to strengthen. This study aims to analyze the linkages between the Mining and Quarrying sector and other sectors in the East Kalimantan economy, as well as to measure its impact on output, income, and employment. The method used is Input-Output analysis through forward and backward linkages, as well as labor and income multipliers. The results show that the Mining and Quarrying sector has strong forward linkages, with a Forward Linkage value of 2.7086, and backward linkages of 1.4138. This indicates that the mining sector plays a crucial role as a provider of inputs to other sectors while also serving as a user of inputs from supporting sectors. In terms of employment, the mining sector employs only about 0.40 people per Rp1 billion of output, reflecting the sector’s capital-intensive nature. These findings underscore the need to strengthen downstream processing, deepen local supply chains, and diversify labor-intensive sectors to foster more inclusive and sustainable economic growth in East Kalimantan.